The Influence of Transformational Leadership, Work Motivation and Organizational Commitment on the Performance of State Junior High School Teachers in Jambi City - Dina Novita; Supian Ramli; K.A. Rahman (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of principals' transformational leadership on work motivation, organizational commitment, and teacher performance, as well as the influence of work motivation and organizational commitment on the performance of teachers at public junior high schools in Jambi City. This research employed a quantitative approach using a survey method. The population consisted of 217 teachers from four public junior high schools in Jambi City, selected using a purposive sampling technique. The data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results indicate that transformational leadership has a significant effect on teachers' work motivation with a coefficient value of 0.498, a t-statistic of 6.152, and a p-value of 0.000. Transformational leadership also has a significant effect on teacher performance with a coefficient value of 0.156, a t-statistic of 2.186, and a p-value of 0.029. In addition, transformational leadership significantly affects organizational commitment with a coefficient value of 0.338, a t-statistic of 5.261, and a p-value of 0.000. Furthermore, work motivation has a significant effect on teacher performance with a coefficient value of 0.174, a t-statistic of 3.023, and a p-value of 0.003, and it also significantly affects organizational commitment with a coefficient value of 0.381, a t-statistic of 7.400, and a p-value of 0.000. Organizational commitment also has a significant effect on teacher performance with a coefficient value of 0.476, a t-statistic of 7.450, and a p-value of 0.000. The coefficient of determination (R²) shows that transformational leadership explains 24.8% of the variance in work motivation, 38.8% of organizational commitment, and 47.8% of teacher performance. The findings indicate that principals' transformational leadership plays an important role in improving teachers' work motivation, organizational commitment, and performance. In addition, work motivation and organizational commitment are proven to be important factors in enhancing teacher performance in public junior high schools in Jambi City.